Right recurrent patellar dislocation treated surgically via the Campbell method: an illustrative case report - Katkani, Anmol; Modi, Lomesh P.; Gupta, Vatsal A.; Desai, Sarvang; Surana, Muskan (International Journal of Research in Orthopaedics, 2025)
Recurrent patellar dislocation is a disabling condition, particularly prevalent among adolescents and young adults, often caused by anatomical abnormalities such as trochlear dysplasia or prior trauma. Surgical intervention, including the Campbell technique, is indicated when conservative management fails. A 24 years old male with recurrent right patellar dislocation and trochlear dysplasia (Dejour type B) underwent proximal realignment via the Campbell technique. The procedure involved creating a medial capsular flap, reinforcing it with Fiber wire sutures and repositioning it to stabilize the patella. Postoperative immobilization and rehabilitation were implemented. Surgical stabilization using the Campbell technique is a viable option for recurrent patellar dislocation, offering excellent functional outcomes in anatomically predisposed patients. Comprehensive evaluation and tailored surgical planning remain essential for optimal results.